2020
DOI: 10.1002/cbdv.202000503
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from Citrus changshan‐huyou and Their Anti‐Inflammatory Activities

Abstract: A systematically chemical investigation of Citrus changshan-huyou Y.B.Chang resulted in the isolation and structure determination of twelve known natural products, including limonoid,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…NKT is one of the important bioactive integrands of the medicinal plant A. oxyphylla. It has also been isolated from the edible fruit, Citrus changshan-huyou [9,46]. It is abundantly present in fruits and peels and is easily extracted by ethanol [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…NKT is one of the important bioactive integrands of the medicinal plant A. oxyphylla. It has also been isolated from the edible fruit, Citrus changshan-huyou [9,46]. It is abundantly present in fruits and peels and is easily extracted by ethanol [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Modern studies have indicated flavonoids are representative and dominant phenolic compounds isolated from CACH. Most of the flavonoids in it were in the form of flavanone glycosides, such as naringin (1), neohesperidin (4), narirutin (5), eriocitrin (7), neoeriocitrin (10), PMFs (11), and tangeretin (3) etc., (Hu et al, 2020;Zhou et al, 2021).…”
Section: Phenols and Their Derivativesmentioning
confidence: 99%
“…It grows rapidly, and its fruit expands mainly in June to July and September. Its expansion rate slows down after mid-September and harvested in November ( Hu et al, 2020 ). It has the characteristics of high yield, frost resistance, strong adaptability and storage resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as authentic medicinal material, it was selected as the new "Zhejiang Eight Flavours". Citrus changshan-huyou has an excellent antiin ammatory effect, therefore, it is also commonly used in the clinical treatment of in ammatory bowel disease and enteropathy caused by NSAIDs (23). However, because of the strict processing requirements of Citrus changshan-huyou, its extract PTFC may have a better prospect for clinical promotion.…”
Section: Introductionmentioning
confidence: 99%